2018
DOI: 10.1021/acsaem.8b01660
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Power Factor for Inherently Poor Thermal Conductor Ag8GeSe6 by Replacing Ge with Sn

Abstract: Superionic argyrodites have been identified as thermoelectric materials with inherent ultralow lattice thermal conductivity because of liquid-like behavior of cations in a relatively larger unit cell. The major drawback for these as potential thermoelectric materials is low carrier concentration and low electrical conductivity, which however can be improved by controlling the compositions while keeping the advantageous poor thermal conductivity intact. Here, we report ∼8 times enhancement of thermoelectric pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…5a ). It is observed that the n H value enhances from 1.93 × 10 16 cm −3 at x = 0 to 8.61 × 10 16 cm −3 at x = 0.1, comparable to that reported by Acharya et al 50 Usually, the mobility μ decreases because of ionized impurity and carrier scattering. 51–53 However, the mobility μ in the present work is laying in the range of 1.17 × 10 2 cm 2 V −1 s −1 and 1.34 × 10 2 cm 2 V −1 s −1 when x value increases from 0 to 0.075 and remains almost unchanged, and then it drops as the x value exceeds 0.075.…”
Section: Resultssupporting
confidence: 88%
“…5a ). It is observed that the n H value enhances from 1.93 × 10 16 cm −3 at x = 0 to 8.61 × 10 16 cm −3 at x = 0.1, comparable to that reported by Acharya et al 50 Usually, the mobility μ decreases because of ionized impurity and carrier scattering. 51–53 However, the mobility μ in the present work is laying in the range of 1.17 × 10 2 cm 2 V −1 s −1 and 1.34 × 10 2 cm 2 V −1 s −1 when x value increases from 0 to 0.075 and remains almost unchanged, and then it drops as the x value exceeds 0.075.…”
Section: Resultssupporting
confidence: 88%
“…Here, the thermal and ionic transport, as well as the vibrational properties, of nine Ag + argyrodite compositions are investigated, some of which are promising high-efficiency thermoelectric materials. [25,[34][35][36] This work aims to decouple the influences of ionic transport, structural complexity, and anharmonicity on the vibrational character and corresponding thermal conductivity of these fast ion conductors. By experimentally quantifying ionic conductivity and thermal conductivity, in conjunction with state-of-the-art computational methods, we are able to address the following questions: 1) Are significant diffuson contributions to thermal conductivity present in the here investigated fast ionic conductors?…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In the past few decades, many strategies have been employed to improve the zT value by improving α 2 σ through band engineering [ 4–8 ] and introducing resonant levels in the electron density of states by doping. [ 9,10 ] Meanwhile, nanostructuring, [ 11 ] nanocomposites, [ 12 ] complex crystal structuring, [ 13,14 ] and the phonon softening technique [ 15 ] have been employed to reduce κ tot . For power generation and refrigeration, various thermoelectric materials have been reported to have high zT ≥ 1, including Bi 2 Te 3 , [ 16,17 ] PbTe, [ 18,19 ] SnTe, [ 20,21 ] SnSe, [ 22 ] and SiGe.…”
Section: Introductionmentioning
confidence: 99%